Edukasi Tanda Bahaya Kehamilan Pada Kelas Ibu Hamil Puskesmas Cipaku - Asmarani, Sri Utami; Purwati, Ayu Endang; Yulianingsih, Ade Putri (Kolaborasi: Jurnal Pengabdian Masyarakat, 2024)
Introduction: The success of maternal health programmes can be assessed through the key indicator of maternal mortality rate (MMR). Maternal mortality is defined as all deaths during the period of pregnancy, labour, and puerperium that are caused by its management but not due to other causes such as accidents or incidentals. Knowledge of danger signs in pregnancy is very helpful in reducing MMR, because by knowing the danger signs in pregnancy a pregnant woman will seek health services more quickly so that risks in pregnancy will be detected and handled earlier. Objective: This community service was carried out to increase the knowledge of pregnant women in the Cipaku Health Centre pregnant women class about danger signs in pregnancy. Method: The method of implementing this community service by providing education in the form of lectures, discussions and answering questions from participants. Result: The results of the pre-test given before the provision of education showed that there were 6 (60%) mothers who were able to answer the pre-test questions correctly. The post test was given after the provision of education, where the results showed that there were 10 (100%) pregnant women who could increase their knowledge about danger signs in pregnancy. Conclusion: Pregnant women are very enthusiastic in participating in activities that include providing education about pregnancy danger signs. Community service activities also increase the knowledge of pregnant women so that pregnant women can detect danger signs in pregnancy and immediately check with health workers if there are danger signs of pregnancy.